Boar rearing: the influence of group vs individual penning from weaning to 27 weeks of age - S T Tonn; J V Craig; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1982)
We compared mating performance and soundness of feet and legs of boars which were reared in group vs individual pens. Individually penned boars consumed more feed from 6 to 12 weeks of age and were heavier at 12 weeks of age. However, individually penned boars also were more unsound and tended to score lower in mating tests.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Boar rearing; Group vs individual penning